2010
DOI: 10.1111/j.1745-459x.2009.00254.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Profiling of Changes in Wheat and Whole Wheat Bread During a Prolonged Period of Storage

Abstract: A sensory profile of wheat and whole wheat pan bread with extented shelf life was conducted to characterize sensory changes during a 3‐week storage period. Variation between assessors was also assessed together with repeatability of the profile. The robustness in the sensory profile was determined by comparing two sensory trials 4 months apart (with six assessors participating in both trials). Initially, assessors agreed on a consensus list of 14 attributes (wheat) and 17 attributes (whole wheat). Multivariate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Albeit significant, the oxidative changes in the whole wheat bread were relatively minor as already demonstrated using sensory profiling of similar bread products stored up to 3 weeks (Jensen et al, 2010). Attributes characterising the stored bread were 'aged', 'dusty', 'rancid', 'sickly sweet', and 'bitter', as also found for other foods for which oxidative changes are important contributory to flavour defects.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Albeit significant, the oxidative changes in the whole wheat bread were relatively minor as already demonstrated using sensory profiling of similar bread products stored up to 3 weeks (Jensen et al, 2010). Attributes characterising the stored bread were 'aged', 'dusty', 'rancid', 'sickly sweet', and 'bitter', as also found for other foods for which oxidative changes are important contributory to flavour defects.…”
Section: Resultsmentioning
confidence: 84%
“…Control of bread firming and microbial activity mean that other quality parameters may determine the shelf life of baked products. It has previously been shown that changes in aroma, flavour and taste occur during storage of whole wheat bread (Holtekjoelen, Baevre, Roedbotten, Berg, & Knutsen, 2008;Jensen, Oestdal, & Thybo, 2010). In these studies aroma and flavour attributes such as 'acidic', 'off', 'rancid' and 'dust' together with the taste attributes 'sweet' and 'bitter' were found to increase with storage time.…”
Section: Introductionmentioning
confidence: 97%
“…Table 3 summarises the proposed attributes considering the comments obtained from the 52 assessors, the visio-tactile perception and texture seems to be the most decisive criterion of consumer acceptability of broa. In fact, the texture of the bread crumb is related to the perception of quality (Gámbaro et al, 2002;Jensen et al, 2010).…”
Section: Sensory Quality Responsesmentioning
confidence: 99%
“…Higher cutoff values were reported by Silva et al (2009), ranging from 27.34 to 40.21 N for cereal bars developed with passion residues. According to with Jensen et al (2010), the textural properties are strongly influenced by the size or the structure of cells and are strongly determined by the quantity and quality of gluten or other substances in bulk. In addition, the texture attributes undoubtedly contribute greatly in product freshness of perception by consumers.…”
Section: Resultsmentioning
confidence: 99%